Japanese politics fixed and floating worlds - Hoye, Timothy (Prentice Hall, 1999)
Suitable for upper level undergraduate and graduate level courses on Japanese politics, comparative Asian political systems, or Pacific Rim systems offered through Political Science, and History, this book provides a comprehensive introduction to the political structure of modern Japan.